Inter-rater reliability of measures to characterize the tobacco retail environment in Mexico - Marissa G Hall; Christy Kollath-Cattano; Luz Myriam Reynales-Shigematsu; James F Thrasher (Instituto Nacional de Salud Pública, 2015)
Objective. To evaluate the inter-rater reliability of a data collection instrument to assess the tobacco retail environ- ment in Mexico, after major marketing regulations were implemented. Materials and methods. In 2013, two data collectors independently evaluated 21 stores in two census tracts, through a data collection instrument that assessed the presence of price promotions, whether single cigarettes were sold, the number of visible advertisements, the pre- sence of signage prohibiting the sale of cigarettes to minors, and characteristics of cigarette pack displays. We evaluated the inter-rater reliability of the collected data, through the calculation of metrics such as intraclass correlation coefficient, percent agreement, Cohen's kappa and Krippendorff's alpha. Results. Most measures demonstrated substantial or perfect inter-rater reliability. Conclusions. Our results indicate the potential utility of the data collection instrument for future point-of-sale research.